Keamanan Siber Dalam Sistem Informasi Berbasis Cloud: Tantangan dan Solusi - Tanjung, Abdul Majid; Lase, Wisdom Anugerah; Zega, Osadikman; Lafau, Resti Oktaviani (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
With the rapid development of cloud computing technology, cybersecurity has become one of the main challenges in the implementation of cloud-based information systems. This article aims to analyze the threats commonly encountered in cloud systems and provide recommendations to improve security levels on these platforms. The research method used in this study is literature review and case analysis. The findings show that cybersecurity threats, such as data breaches and information leakage, are the main issues that need to be addressed through the use of better encryption technologies, strict identity management, and real-time system monitoring. The study also suggests the implementation of comprehensive security policies as an effective mitigation step.